Erosive Lichen Sclerosus—A Clinicopathologic Subtype. Issue 3 (July 2021) - Day, Tania; Otton, Geoffrey; Dennerstein, Graeme; Tran, Hong; Scurry, James
Abstract : Objective: The aim of the study was to identify whether erosive lichen sclerosus (LS) is a distinct clinicopathologic subtype. Materials and Methods: The pathology database was searched for "erosion, " "erosive, " "ulcer, " and "lichen sclerosus." Inclusion criteria were histopathologic diagnosis of LS and erosion or ulcer overlying a band of hyalinization and/or fibrosis. Exclusions were concurrent neoplasia and insufficient tissue. Histopathologic review documented site, epithelial thickness, adjacent epidermal characteristics, infiltrate, and dermal collagen abnormality. Clinical data included demographics, comorbidities, examination findings, microbiologic results, treatment, and response. Results: Ten examples of erosive LS and 15 of ulcerated LS occurred in 24 women with a mean age of 67 years. Ulcerated LS was associated with diabetes and nontreatment at time of biopsy. Clinicians identified red patches in all but 1 case of erosive LS. Ulcerated LS was documented as fissure, ulcer, or white plaque, with 8 (53%) described as lichenified LS with epidermal breaches. Erosive LS favored hairless skin with normal adjacent stratum corneum sloping gently into erosion, whereas most ulcers in LS had an abrupt slope from hair-bearing skin. All cases were treated with topical steroids; 2 patients with erosive LS and 10 with ulcerated LS also had oral antifungals, topical estrogen, antibiotics, and/or lesional excision. Treatment yielded complete resolution in 50%. Conclusions: Erosive LS is an unusual clinicopathologic subtype characterized by red patches on hairless skin seen microscopically as eroded epithelium overlying a band of hyalinized or fibrotic collagen. In contrast, ulcerated LS is usually a traumatic secondary effect in an uncontrolled dermatosis.